A Content Analysis of the Reading Activities in â€œBright 2â€an English Textbook for Junior High School Students - Sucipto, Sucipto; Cahyo, Septian Dwi (English Language Teaching Educational Journal, 2019)
This study aimed to analyze reading activities in ?Bright 2? an English textbook for junior high school students grade VIII in Indonesia by using Bloom?s revised taxonomy. A content analysis was conducted to achieve the research purpose. The findings show that the textbook has dominant reading activities on the cognitive process ?analyze? 27% and ?apply? 21% of the total 145 reading activities, respectively.  The number of higher and lower cognitive processes in this textbook is almost balanced on 49% of higher order thinking skills and 51% of lesser order thinking skills correspondingly. There is a slight difference between the number higher thinking process and lower thinking process since most reading activities are on ?analyze?, which is belong to the higher thinking process while the second most frequent reading activities are ?apply?, the lower thinking process. Meanwhile, ?apply? and ?analyze? is placed on the 3rd and 4th in the taxonomy, it means that the textbook emphasizes the middle cognitive thinking process of Bloom?s revised taxonomy, which is formed by ?apply? and ?analyze?  thinking process.